2007
DOI: 10.1248/jhs.53.190
|View full text |Cite
|
Sign up to set email alerts
|

Preventive Effects of Bee Pollen Cistus ladaniferus Extract on Bone Loss in Streptozotocin-Diabetic Rats In Vivo

Abstract: The effect of bee pollen cistus extract on serum and bone biochemical components in streptozotocin (STZ)-diabetic rats was investigated. The water-solubilized extracts were obtained from the bee pollen of Cistus ladaniferus. Rats received a single subcutaneous administration of STZ (6.0 mg/100 g body weight), and then the animals were orally administered water-solubilized extract (5, 10, or 20 mg/100 g body weight) of bee pollen cistus once daily for 14 days. The administration of STZ caused a significant decr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 33 publications
0
16
0
1
Order By: Relevance
“…Gayathri and Kannabiran (2008) showed that in STZ-diabetic rats, there was a significant increase in the serum Na, K and Ca. Uchiyama and Yamaguchi (2003) and Yamaguchi et al (2007) demonstrated that the levels of serum Ca were increased in STZ-diabetic rats. Yanardag et al (2005) and Ozsoy-Sacan et al (2006) reported that in the STZ-diabetic rats, the blood Na and K levels were statistically increased.…”
Section: Discussionmentioning
confidence: 99%
“…Gayathri and Kannabiran (2008) showed that in STZ-diabetic rats, there was a significant increase in the serum Na, K and Ca. Uchiyama and Yamaguchi (2003) and Yamaguchi et al (2007) demonstrated that the levels of serum Ca were increased in STZ-diabetic rats. Yanardag et al (2005) and Ozsoy-Sacan et al (2006) reported that in the STZ-diabetic rats, the blood Na and K levels were statistically increased.…”
Section: Discussionmentioning
confidence: 99%
“…The intake of cistus extract has preventive effects on bone loss in diabetic state and ovariectomized rats, 13,14) suggesting a role in the prevention of osteoporosis.…”
Section: Discussionmentioning
confidence: 99%
“…10) Royal jelly does not have an inhibitory effect on osteoclastogenesis in mouse marrow culture in vitro, 12) so that the effect of bee pollen on bone metabolism may thus be unique among beerelated products. The intake of bee pollen cistus extract has been demonstrated to have preventive effects on bone loss induced in the diabetic state 13) and ovariectomized rats, 14) suggesting a useful role in the prevention of osteoporosis with aging.…”
Section: Introductionmentioning
confidence: 99%
“…duce bone loss, 22) has been shown to have preventive effects on bone loss with diabetes in vivo. 20) We examined the preventive effect of cistus extract on bone loss in OVX rats, a model of osteoporosis, in vivo, furthermore.…”
Section: Discussionmentioning
confidence: 99%
“…19) The intake of bee pollen cistus extract has been shown to have preventive effects on bone loss in streptozotocin-diabetic rats, and the intake has partial restorative effects on serum biochemical findings with the diabetic state in vivo. 20) This study was undertaken to determine whether the intake of bee pollen cistus extract has preventive effects on bone loss induced in ovariectomized (OVX) rats, a model of osteoporosis, in vivo.…”
Section: Introductionmentioning
confidence: 99%